Der Handel von Kreditrisiken: Eine neue Dimension des Kapitalmarktes - Jan Pieter Krahnen (Goethe University Frankfurt, Center for Financial Studies (CFS), 2005)
This paper makes an attempt to present the economics of credit securitization in a nontechnical way, starting from the description and the analysis of a typical securitization transaction. The paper sketches a theoretical explanation for why tranching, or nonproportional risk sharing, which is at the heart of securitization transactions, may allow commercial banks to maximize their shareholder value. However, the analysis makes also clear that the conditions under which credit securitization enhances welfare, are fairly restrictive, and require not only an active role of the banking supervisiory authorities, but also a price tag on the implicit insurance currently provided by the lender of last resort.
urn:nbn:de:hebis:30-10829
Keywords: D82; G21; D74; 330; Kreditrisiko; Finanzderivat; Securitization; Wertpapierhandel